2012
DOI: 10.1039/c2lc20967e
|View full text |Cite
|
Sign up to set email alerts
|

Electrical sorting of Caenorhabditis elegans

Abstract: The nematode (worm) C. elegans is one of the widely studied animal model organisms in biology. It develops through 4 larval stages (L1-L4) in 2 to 3 days before becoming a young adult. Biological assays involving C. elegans frequently require a large number of animals that are appropriately staged and exhibit a similar behaviour. We have developed a new method to synchronize animals that relies on the electrotactic response (electric field-induced motion) of C. elegans to sort them in parallel based on their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 30 publications
0
82
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22] In previous work from our group, we designed a simple microfluidic device to examine the swimming behaviors of C. elegans under electric fields, termed electrotaxis, and demonstrated that changes in movement are reliable indicators of neurodegeneration and harmful effects of toxic chemicals on C. elegans health. [23][24][25] However, the inherent manual operation of the devices makes the screening process labor intensive and time consuming, which limits largely the practical application of the method. [23][24][25] In order to enable widespread use of the electrotactic assay, we have addressed the current limitations and developed an entirely new automated microfluidic system, which can perform electrotaxis assay for a batch of worms, without human intervention, one worm at a time while substantially increasing the throughput of analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22] In previous work from our group, we designed a simple microfluidic device to examine the swimming behaviors of C. elegans under electric fields, termed electrotaxis, and demonstrated that changes in movement are reliable indicators of neurodegeneration and harmful effects of toxic chemicals on C. elegans health. [23][24][25] However, the inherent manual operation of the devices makes the screening process labor intensive and time consuming, which limits largely the practical application of the method. [23][24][25] In order to enable widespread use of the electrotactic assay, we have addressed the current limitations and developed an entirely new automated microfluidic system, which can perform electrotaxis assay for a batch of worms, without human intervention, one worm at a time while substantially increasing the throughput of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] However, the inherent manual operation of the devices makes the screening process labor intensive and time consuming, which limits largely the practical application of the method. [23][24][25] In order to enable widespread use of the electrotactic assay, we have addressed the current limitations and developed an entirely new automated microfluidic system, which can perform electrotaxis assay for a batch of worms, without human intervention, one worm at a time while substantially increasing the throughput of analysis. This system can load, isolate, perform electrotaxis assay, and flush C. elegans in a computer-controlled sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Rezai et al spatially separated different worms in a simple planar microchannel with a narrowed trap region based on the age-dependent or stagedependent electrotactic responses of worms. 25 In addition, continuous sorting can be achieved in a parallel manner. Han et al proposed another sorting strategy based on the size-dependent motility and electrotaxis of worms in a microstructured channel.…”
Section: Electrotactic Sortingmentioning
confidence: 99%
“…Using this device, authors sorted the young adult worms from older worms, young adult worms from larval staged worms and wild-type young adult worms from mutant worms. Although the sorter works at a selectivity of ~90% for worms of different age and mutants, multi-stage sorting of worms can potentially overcome this issue [38].…”
Section: Application Of Electrotaxis Behavior In Worm Researchmentioning
confidence: 99%
“…Handful of devices/setup and microfluidic devices had been introduced to scientific community which can sort worms based on electro-sensation behavior of worm into age, size and locomotion defective groups. Rezai et al (2012) introduced a microfluidic device that can sort worms using differential electrotactic response of the worm at different age. The microfluidic device created contains an electrical trap with narrow microchannel, which enhances the EF in the narrow channel when compared to the wider channel on either side.…”
Section: Application Of Electrotaxis Behavior In Worm Researchmentioning
confidence: 99%